2021
DOI: 10.3390/agriculture11090851
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lameness on Attributes of Feeding Registered with Noseband Sensor in Fresh Dairy Cows

Abstract: We hypothesized that lameness in fresh dairy cows (1–30 days after calving) has an impact on attributes of feeding registered with a noseband sensor. The aim of this study was to investigate the impact of lameness in fresh dairy cows on attributes of feeding (registered with the RumiWatch noseband sensor): rumination time (RT), drinking time (DT), eating time (ET), rumination chews (RC), eating chews (EC), chews per minute (CM), drinking gulps (DG), bolus count (B), and chews per bolus (CB). The measurement re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, Abeni and Galli [49] discovered that the greatest reduction in daylight RT (from 0800 h to 2000 h) varied from 49 % for cows in the early stages of lactation to 45 % for cows in the plateau periods, although the range of decline in daily RT varied from 49 % to 45 %. In our past study we found, that on the day of lameness identification, reductions in rumination time, eating time, rumination chews, drinking time, and bolus count in the lame group may act as lameness markers [50].…”
Section: Discussionmentioning
confidence: 86%
“…However, Abeni and Galli [49] discovered that the greatest reduction in daylight RT (from 0800 h to 2000 h) varied from 49 % for cows in the early stages of lactation to 45 % for cows in the plateau periods, although the range of decline in daily RT varied from 49 % to 45 %. In our past study we found, that on the day of lameness identification, reductions in rumination time, eating time, rumination chews, drinking time, and bolus count in the lame group may act as lameness markers [50].…”
Section: Discussionmentioning
confidence: 86%
“…However, Abeni and Galli [51] reported that the greatest reduction in daylight RT (from 0800 to 2000 h) varied from 49% for cows in the early stages of lactation. In our past study, we found that on the day of lameness identification, reductions in rumination time, eating time, rumination chews, drinking time, and bolus count in the lame group could act as lameness markers [52].…”
Section: Discussionmentioning
confidence: 88%
“…Lame cows consume less feed because they spend so much time lying down, which lowers their milk production (Mohammed B. Sadiq Antanaitis et al, 2021). Feed intake may decrease even more as a result of the increased pain brought on by being unable to stand or move to eat, which could lead to a further decline in milk production.…”
Section: Discussionmentioning
confidence: 99%
“…Lameness is de ned as any infectious or non-infectious foot or leg condition that impairs cow mobility, posture, and gait (Heinonen et al, 2013;Weber et al, 2013;Elliott et al, 2015;Sadiq et al, 2021). The most common cause of lameness in dairy cows is claw lesions, which can be non-infectious (white line disease, sole ulcer) or infectious (digital dermatitis, interdigital dermatitis, heel erosion, and interdigital phlegmon (foot rot) (L. D. ; van der Linde et al, 2010; Antanaitis et al, 2021;Sheferaw et al, 2021). Lameness in cows starts a negative chain reaction that has many consequences for both the farmer and the cow, including reduced milk yield (about 20% reduction), loss of reproduction, lack of weight gain, and, in some cases, animal culling (Randall et Lameness has been identi ed as the most serious welfare issue in dairy cows, and its observation is the most representative animal-based indicator of dairy cattle well-being (Weber et al, 2013;Nalon and Stevenson, 2019).…”
Section: Introductionmentioning
confidence: 99%